Magnetic Resonance Image Guided Focused Ultrasound Thalamotomy. A Single Center Experience With 160 Procedures - Lak, Asad M.; Segar, David J.; McDannold, Nathan; White, Phillip Jason; Cosgrove, Garth Rees (Frontiers in Neurology, 2022)
Introduction MRgFUS thalamotomy has gained popularity as an FDA approved, non-invasive treatment for patients with Essential Tremor and tremor predominant Parkinson's Disease. We present our initial clinical experience with 160 consecutive cases of MRgFUS thalamotomy and describe the clinical outcomes with long term follow-up. Methods A retrospective chart review of all patients who underwent MRgFUS thalamotomy at our institution was performed. CRST Part A tremor scores were obtained pre-operatively and at each follow-up visit along with an assessment of side effects (SE). All patients had a post-operative MRI within 24 h to determine the location, size, and extent of the MRgFUS lesion. Results One hundred and sixty unilateral MRgFUS Thalamotomies (Left, n = 128; Right, n = 32) were performed for medically refractory essential Tremor (n = 150) or tremor predominant Parkinson's disease (n = 10). Mean age at surgery was 75 Years (range: 48-93) and the mean skull density ratio (SDR) was 0.48 (range: 0.32-0.75; median: 0.46). In ET patients, both rest and postural tremor was abolished acutely and remained so at follow-up whereas intention tremor was reduced acutely by 93% below baseline, 87% at 3 months, 83.0% at 1-year, and 78% at 2 years. On post-operative day 1, the most common SE's included imbalance (57%), sensory disturbances (25%), and dysmetria (11%). All adverse events were rated as mild on the Clavien-Dindo Scale and improved over time. At 2-years follow-up, imbalance was seen in 18%, sensory disturbance in 10% and dysmetria in 8% patients. Mean clinical follow-up for all patients was 14 months (range: 1-48 months). Conclusion MRgFUS thalamotomy is a safe and effective procedure for long term improvement of unilateral tremor symptoms, with the most common side-effects being imbalance and sensory disturbance.